Teachers’ Experiences in Organizing the Process of Assessment and Self-Assessment of Students in Natural Sciences Lessons - Tomėnienė, Laima; Vaičiūnienė, Asta (Technium Social Sciences Journal, 2023)
The article analyses the experiences of teachers in organizing assessment and self-assessment processes in natural sciences lessons. In order to compare the teacher’s assessment and the student’s self-assessment, the study relies on the concept of assessment as learning. The research participants are primary education teachers who organize natural sciences lessons for fourth-grade students. The study is based on the methodology of participatory action research. During the action research, the role of the teacher and the student in achieving the harmony of assessment and self-assessment was revealed, four main stages of the student’s self-assessment of the lesson were distinguished as well as the factors promoting and limiting the harmony of assessment and self-assessment. It was emphasized that during the educational process, teachers must constantly monitor students, record individual progress in a chosen way, analyse the results, and discuss them with students. Collaboration with colleagues becomes important, which helps to collect and analyse data, organize joint activities together, discuss results, examine challenges, and recommend solutions.